2019
DOI: 10.1037/ort0000391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action in AWARE: A culturally informed intervention for 1.5- and 2nd-generation Asian American women.

Abstract: Young Asian American women have high rates of depression and suicidality; however, few interventions address the urgent need for culturally informed care. Asian Women’s Action for Resilience and Empowerment (AWARE) aims to be the first gender and culturally specific group psychotherapy intervention designed to improve mental and sexual health in Asian American women with trauma. This article specifically focuses on identifying the mechanisms of action that were responsible for improving mental health and well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Numerous studies have demonstrated that social stigma, shame, and "saving face" often prevent Asian and Asian American individuals from seeking mental health care. [20][21][22][23][24] Meanwhile, the risk of suicide following cancer diagnosis among Hispanic persons was no different or potentially even lower compared with the general population, with a 37% lower risk in the highestincome counties. This finding may be partially explained by the Hispanic health paradox, a wellestablished epidemiologic finding that Hispanic people tend to have lower mortality rates compared with non-Hispanic people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that social stigma, shame, and "saving face" often prevent Asian and Asian American individuals from seeking mental health care. [20][21][22][23][24] Meanwhile, the risk of suicide following cancer diagnosis among Hispanic persons was no different or potentially even lower compared with the general population, with a 37% lower risk in the highestincome counties. This finding may be partially explained by the Hispanic health paradox, a wellestablished epidemiologic finding that Hispanic people tend to have lower mortality rates compared with non-Hispanic people.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that cultural factors may be involved in this result. Numerous studies have demonstrated that social stigma, shame, and “saving face” often prevent Asian and Asian American individuals from seeking mental health care . Meanwhile, the risk of suicide following cancer diagnosis among Hispanic persons was no different or potentially even lower compared with the general population, with a 37% lower risk in the highest-income counties.…”
Section: Discussionmentioning
confidence: 99%
“…AWARE is directed toward Asian American women who have experienced trauma (Rivera et al, 2019). AWARE covers a variety of health topics, including depression, suicidality, sexual risk behaviors, and substance use (Hahm et al, 2017; Rivera et al, 2019). It effectively teaches clients to utilize the mind–body connection that is rooted in many Asian cultures to create an environment and mindset that is more conducive to improving overall mental health (Hahm et al, 2017).…”
Section: Evidence For Third-wave Therapy Efficacy In Substance Usementioning
confidence: 99%
“…In general, mechanisms are considered as causal links between treatment and outcomes. Rivera et al (2019) analyze 16 AWARE cohorts' postintervention focus group discussion after participants completed eight sessions of group psychotherapy. This study identified that the mechanisms of action that contribute to the improvement of mental health outcomes were four distinctive and culturally specific mediators: (a) psychoeducation on disempowering parenting, (b) the reduction of mental illness-related stigma, (c) community and relationship building, and (d) a heightened sense of empowerment.…”
Section: Culturally Adapted Intervention Versus Culturally Grounded I...mentioning
confidence: 99%
“…The second article of this special section, Rivera et al (2019) explored the therapeutic mechanisms of AWARE intervention. Ideal psychotherapy research not only illuminates the efficacy or effectiveness of its intervention, but it also reveals the mediators of therapeutic change (Kraemer, Wilson, Fairburn, & Agras, 2002).…”
Section: Introductionmentioning
confidence: 99%